CEO Compensation and Audit Opinion ‘Going Concern’ Effect Banking Performance Using Data Envelopment Analysis (DEA) Method? - Farisha Eva Apriani; R. Nelly Nur Apandi (Nusantara Science and Technology Proceedings, 2020)
Company performance as an achievement of finished tasks illustrates the company's financial condition, which can be analyzed by financial analysis tools. This study aimed to determine the impact of CEO compensation and audit opinion 'going concern' on the performance of banks listed on the BEI from 2014 to 2019, as well as to evaluate the performance using the Data Envelopment Analysis (DEA) tool. Furthermore, this study also aimed to examine the effect of audit opinion 'going concern,' which was determined as the moderation variable to the relationship between the CEO's compensation and banking performance. The study used a quantitative type. Subjects examined were banks listed in BEI and reported their financial statements consistently from 2014 to 2019. The data analysis was using Partial Least Square (PLS). Based on the study results, it is discovered that CEO's compensation positively and significantly affected banking performance on the studied year, audit opinion 'going concern' significantly affected banking performance, and the audit opinion 'going concern' that determined as the moderation variable could not strengthen or weaken the relationship between CEO's compensation and banking performance.